2021
DOI: 10.5469/neuroint.2020.00416
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from a Fulminant Case of Reversible Cerebral Vasoconstriction Syndrome: Past Medical History Misleads the Diagnosis and Intra-Arterial Milrinone Offers Diagnostic Utility

Abstract: A 34-year-old post-partum female having dermatomyositis developed headache and became comatose after a seizure episode. Magnetic resonance imaging of brain showed a massive left ganglio-capsular bleed for which decompressive surgery was done. Computed tomographic angiography showed multiple foci of narrowing and irregularities in distal cerebral vessels. In view of dermatomyositis, the diagnosis of vasculitis was considered and pulse therapy of intravenous methylprednisolone was started. The patient, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Literature review demonstrates that thus far, pregabalin and gabapentin, 9,10,15 fentanyl, 11 lidocaine, 18 and magnesium 13,16 are the only medications to have any published findings demonstrating some level of headache improvement in post‐SAH patients, while other studies demonstrate little to no benefit for other opioids, 4,6,11,13 acetaminophen, 6,13 dexamethasone, 3,7 ketorolac, 13 ibuprofen, 13 or A/B/C; the findings of these studies with more details are summarized in Table 1 along with interventions including local nerve blockade, CSF drainage, and others 13 . Milrinone infusion has been used in some institutions for particularly severe headaches, where reversible cerebral vasospasm of various causes (not necessarily aneurysmal SAH) is thought to be etiologic 25,74,75 . Thus, its current use in post‐SAH patients for treating vasospasm 76 may have additional benefit for headache pain, although this has not been specifically studied to our knowledge, although the pathophysiology of these diseases differ.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature review demonstrates that thus far, pregabalin and gabapentin, 9,10,15 fentanyl, 11 lidocaine, 18 and magnesium 13,16 are the only medications to have any published findings demonstrating some level of headache improvement in post‐SAH patients, while other studies demonstrate little to no benefit for other opioids, 4,6,11,13 acetaminophen, 6,13 dexamethasone, 3,7 ketorolac, 13 ibuprofen, 13 or A/B/C; the findings of these studies with more details are summarized in Table 1 along with interventions including local nerve blockade, CSF drainage, and others 13 . Milrinone infusion has been used in some institutions for particularly severe headaches, where reversible cerebral vasospasm of various causes (not necessarily aneurysmal SAH) is thought to be etiologic 25,74,75 . Thus, its current use in post‐SAH patients for treating vasospasm 76 may have additional benefit for headache pain, although this has not been specifically studied to our knowledge, although the pathophysiology of these diseases differ.…”
Section: Methodsmentioning
confidence: 99%
“…13 Milrinone infusion has been used in some institutions for particularly severe headaches, where reversible cerebral vasospasm of various causes (not necessarily aneurysmal SAH) is thought to be etiologic. 25,74,75 Thus, its current use in post-SAH patients for treating vasospasm 76 may have additional benefit for headache pain, although this has not been specifically studied to our knowledge, although the pathophysiology of these diseases differ. Additionally, verapamil is often introduced endovascularly in post-SAH patients experiencing vasospasm, 77 and given that verapamil is commonly utilized in migraine treatment then it is another drug that could potentially be useful in post-SAH headache pain while having a favorable vasoactive profile.…”
Section: Current Treatment Strategiesmentioning
confidence: 99%
“…Previously, it has been reported that the adverse reactions of milrinone including headache, arrhythmia, worsening of muscle weakness, and decreased platelet count were found in clinical patients [8][9][10]. However, clinical trials abroad confirmed that long-term oral milrinone can increase the mortality of patients with HF from non-HF causes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%